Effective secondary fracture prevention: implementation of a global benchmarking of clinical quality using the IOF Capture the Fracture® Best Practice Framework tool. Issue 11 (November 2015) - Javaid, M.; Kyer, C.; Mitchell, P.; Chana, J.; Moss, C.; Edwards, M.; McLellan, A.; Stenmark, J.; Pierroz, D.; Schneider, M.; Kanis, J.; Akesson, K.; et al.
Abstract Summary Fracture Liaison Services are the best model to prevent secondary fractures. The International Osteoporosis Foundation developed a Best Practice Framework to provide a quality benchmark. After a year of implementation, we confirmed that a single framework with set criteria is able to benchmark services across healthcare systems worldwide. Introduction Despite evidence for the clinical effectiveness of secondary fracture prevention, translation in the real-world setting remains disappointing. Where implemented, a wide variety of service models are used to deliver effective secondary fracture prevention. To support use of effective models of care across the globe, the International Osteoporosis Foundation's Capture the Fracture® programme developed a Best Practice Framework (BPF) tool of criteria and standards to provide a quality benchmark. We now report findings after the first 12 months of implementation. Methods A questionnaire for the BPF was created and made available to institutions on the Capture the Fracture website. Responses from institutions were used to assign gold, silver, bronze or black (insufficient) level of achievements mapped across five domains. Through an interactive process with the institution, a final score was determined and published on the Capture the Fracture website Fracture Liaison Service (FLS) map. Results Sixty hospitals across six continents submitted their questionnaires. The hospitals served populations from 20, 000 to 15 million and were a mix of private and publicly funded. Each FLS managed 146 to 6200 fragility fracture patients per year with a total of 55, 160 patients across all sites. Overall, 27 hospitals scored gold, 23 silver and 10 bronze. The pathway for the hip fracture patients had the highest proportion of gold grading while vertebral fracture the lowest. Conclusion In the first 12 months, we have successfully tested the BPF tool in a range of health settings across the globe. Initial findings confirm a significant heterogeneity in service provision and highlight the importance of a global approach to ensure high quality secondary fracture prevention services.